An integrated information systems architecture for the agri‐food industry. Issue 4 (8th September 2020) - Branco, Frederico; Gonçalves, Ramiro; Moreira, Fernando; Au‐Yong‐Oliveira, Manuel; Martins, José
Abstract: As information systems and technologies grow in usage in the agri‐food industry, the same has happened to the relevance of Information Systems (IS) that allow for a parallel control, monitoring and management of the organizations' activities and business processes. As the literature proves, the benefits of implementing adequate and interoperable IS are very numerous and tend to represent a significant determinant regarding the organizations' overall success. Despite this, to the best of our knowledge there currently is no IS architecture designed to serve the specificities of the agri‐food industry. With this study a novel information systems architecture for the agri‐food sector is proposed. The artefact is composed by 12 integrated main components and a set of subcomponents aimed at supporting all the monitoring, control and management activities. In order to validate the proposed architecture a case study was implemented at a mushroom production organization. This allowed us to perceive the ability of our artefact to serve as the basis for the development of IS that address all of the organization's business and environmental needs.